YURIDIKSI PENGADILAN DAN ARBITRASE DALAM MEMERIKSA SUATU SENGKETA DIKAITKAN DENGAN PRINSIP COMPETENCE -COMPETENCE DAN KLAUSUL ARBITRASE - samuel hutabarat (Universitas Katolik Indonesia Atma Jaya, 2021)
The doctrine of the principle of competence explains that arbitration which has jurisdiction in the statement itself is based on the authority to hear and decide an arbitration dispute. The authority possessed by Arbitration even though there is an arbitration clause in a belief as a way of resolving disputes arising in the agreement. The determination of the arbitration authority is related to the validity of an arbitration clause or their agreement arbitration agreement which makes the agreement in question regarding this matter The legal problems in this research relate to the norm vacancies regarding the competence-competence principle in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (hereinafter abbreviated as AAPS Law).Solving research problems using normative legal methods with a legal approach, cases, and analysis of legal concepts.